ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL KONTEKSTUAL MATERI BARISAN ARITMETIKA DITINJAU DARI KEMAMPUAN MATEMATIS - Metilda Triheni Ratna; Agustina Mei; Konstantinus Denny Pareira Meke (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
This study aims to describe and analyze the types of mistakes made by students based on their respective abilities. The research method used is qualitative. The research was conducted at SMA Widya Bhakti, with 6 subjects in class XI MIA. The instrument used was first-semester report card grades for math skills, problem-solving tests and interviews. The data collection technique comes from the answers to written tests and the results of student interviews. Data analysis was carried out qualitatively with the steps of data reduction, presenting data, and drawing conclusions. The results of this study can be used as an effort to improve students' abilities in solving contextual problems in the material of arithmetic sequences. Based on the research results, information was obtained that there were causes of student errors in solving contextual questions based on students' mathematical abilities. One factor that causes high-ability student errors is careless mistakes. Factors causing the errors of students with moderate abilities are errors in reading instructions in questions, conceptual errors, conceptual errors and errors during tests. Causative factors Factors that cause low-ability students' errors are errors in reading instructions, careless errors, application errors, conceptual errors, test errors, and learning errors.